2n+46=9n-10

Simple and best practice solution for 2n+46=9n-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n+46=9n-10 equation:


Simplifying
2n + 46 = 9n + -10

Reorder the terms:
46 + 2n = 9n + -10

Reorder the terms:
46 + 2n = -10 + 9n

Solving
46 + 2n = -10 + 9n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9n' to each side of the equation.
46 + 2n + -9n = -10 + 9n + -9n

Combine like terms: 2n + -9n = -7n
46 + -7n = -10 + 9n + -9n

Combine like terms: 9n + -9n = 0
46 + -7n = -10 + 0
46 + -7n = -10

Add '-46' to each side of the equation.
46 + -46 + -7n = -10 + -46

Combine like terms: 46 + -46 = 0
0 + -7n = -10 + -46
-7n = -10 + -46

Combine like terms: -10 + -46 = -56
-7n = -56

Divide each side by '-7'.
n = 8

Simplifying
n = 8

 

See similar equations:

| g(0)=-9+1 | | g(0)=6.1x-2.2 | | 3x+(3x+5)=x | | g(2)=6.1x-2.2 | | n(39)=7x+4 | | x=3x+(5+3x) | | 12x-23=8x+5 | | q(21)=6-5x | | s(3)=-4x-9 | | 6d+3(1+d)(d-7)=2d | | p(18)=-2.4+6 | | 2x-1=11x-91 | | 2x-5=-7 | | d(31.9)=3.3x-1.1 | | x=x-15 | | -16-5x=8x+17 | | y-18=10 | | 4x=12-7x | | -16-5x=11-8x | | (x-2)2-12=0 | | 15+a=9 | | k+17=8 | | -10z=70 | | 9x^2-7+2=0 | | -6q=102 | | 2x^2-17x=-30 | | X+14=5x-2 | | 9x-3=33 | | -5x+y=139 | | -5(x+y)=139 | | -5(x-y)=139 | | -5x-y=139 | | -5x+y= | | -5(x+y)= | | 3x^3+2=26 | | 3x^3-14x^2+15x=0 | | n=84 | | 7a-11=5a+3 | | -3x-8x+15+35=2x+3 | | 148=4(-4x+2)-12x | | -3x-8x+15+35=2x+3x+19+11 | | 2(x+y)=30 | | 2(x+y)=2 | | 2x+y=30 | | 13x=6x+14 | | 2(3y-5)=14 | | -2y-2=5(y-7) | | 4x^2+12+4=0 | | 4x^2+12+5=0 | | 10x+7=7x+25 | | 7x-14x-19+25=-6x+3x-20+15 | | 5x^2+x=1 | | 8x-17=5x+1 | | 3x+39=11x-57 | | x^4-34x^2+225=p | | x^4-34x^2+225=p | | 9n^2-54n=0 | | x^4-34x^2+225=l | | x^4-34x^2+225=0 | | 15x+7=67 | | K^2+2k-35=0 | | 23x+6=-86 | | -10-6x=8-9x | | 68-3x=2x+8 | | 5n= |